2021
DOI: 10.1186/s12891-021-04704-9
|View full text |Cite
|
Sign up to set email alerts
|

The epidemiology and etiology of adhesive capsulitis in the U.S. Medicare population

Abstract: Background Adhesive capsulitis (AC) of the shoulder, also known as frozen shoulder, causes substantial pain and disability. In cases of secondary AC, the inflammation and fibrosis of the synovial joint can be triggered by trauma or surgery to the joint followed by extended immobility. However, for primary AC the inciting trigger is unknown. The burden of the disorder among the elderly is also unknown leading to this age group being left out of therapeutic research studies, potentially receiving… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
36
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 50 publications
2
36
0
Order By: Relevance
“…n Scott Kulm, PhD 1 Mark T. Langhans, MD, PhD 2 Tony S. Shen, MD 2 David A. Kolin, BS 1 Olivier Elemento, PhD 1 Scott A. Rodeo, MD 2…”
Section: Appendixmentioning
confidence: 99%
See 2 more Smart Citations
“…n Scott Kulm, PhD 1 Mark T. Langhans, MD, PhD 2 Tony S. Shen, MD 2 David A. Kolin, BS 1 Olivier Elemento, PhD 1 Scott A. Rodeo, MD 2…”
Section: Appendixmentioning
confidence: 99%
“…Adhesive capsulitis, or frozen shoulder, is a loss of range of motion with associated pain occurring in the glenohumeral joint of the shoulder, which can develop spontaneously, with no obvious injury or inciting event 1 . It is most common in females 40 to 60 years of age, but has a 1-year prevalence as high as 0.35% 2 and a lifetime prevalence of 10% 3 , making it one of the most common shoulder pathologies. Treatment of adhesive capsulitis can include intra-articular corticosteroid injections, physical therapy, and surgery 4 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The incidence of frozen shoulder among the middle-aged and elderly subjects included in this study was higher than previously reported for the general population. In Europe and the US, frozen shoulder affects an estimated 2% of the general population, with a cumulative incidence of 2.4 cases per 1,000 person-years ( 17 ); in the UK, the annual incidence of frozen shoulder in the general population is ~1.4 per 1,000 individuals ( 18 ); and in the US, the 1-year prevalence of frozen shoulder in individuals aged >65 years is 0.35% ( 19 ). In China, intravenous infusion is the most common mode of administration of medications, nutrients and fluids in inpatients; in 2016, 93.1% of inpatients in urban hospitals in China received intravenous medication administration ( 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…Similar pathology has been reported in both stroke and Parkinson's disease where there is motor dysfunction involving the shoulder. 18,19 Motion is critical to maintain and restore ROM. 13,16 For PALS with shoulder pain, stretching and range of motion exercises are recommended, and strategies to increase compliance can be helpful.…”
Section: Discussionmentioning
confidence: 99%